2019
DOI: 10.22270/jddt.v9i4-s.3378
|View full text |Cite
|
Sign up to set email alerts
|

UV-Spectrophotometric Estimation of Olopatadine hydrochloride in Bulk and Pharmaceutical Dosage Form by Zero, First and Second Order Derivative Methods

Abstract: Simple and accurate UV spectrophotometric methods by Zero, First and Second order derivative method  have been developed and validated for the estimation of Olopatadine hydrochloride in bulk and its pharmaceutical dosage form. The standard and sample solutions of Olopatadine hydrochloride were prepared in methanol and water. Olopatadine hydrochloride was estimated at 299, 289 and 267 nm for the  derivative UV-spectrophotometric method. Beer’s law was obeyed in the concentration range of 20 to 120 μg / mL with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…While these methods provide outstanding detection limits and the capability to analyze OLP degradation by-products, their use is constrained by timeintensive procedures, extended pretreatment steps of the designated compounds or drug, and the need for exceptionally highpurity solvents, along with a requirement for skilled personnel. Also, OLP was detected by a few spectroscopic [34,35], and electrochemical sensors for its detection [36][37][38]. However, the sensitivity of absorbance-based techniques is limited, and the use of electrochemical sensors is hindered by the time-consuming process of synthesizing nanomaterials, such as titanium dioxide nanoparticles, for electrode modification [36].…”
Section: Introductionmentioning
confidence: 99%
“…While these methods provide outstanding detection limits and the capability to analyze OLP degradation by-products, their use is constrained by timeintensive procedures, extended pretreatment steps of the designated compounds or drug, and the need for exceptionally highpurity solvents, along with a requirement for skilled personnel. Also, OLP was detected by a few spectroscopic [34,35], and electrochemical sensors for its detection [36][37][38]. However, the sensitivity of absorbance-based techniques is limited, and the use of electrochemical sensors is hindered by the time-consuming process of synthesizing nanomaterials, such as titanium dioxide nanoparticles, for electrode modification [36].…”
Section: Introductionmentioning
confidence: 99%
“…Olopatadine is official in Indian Pharmacopeia [2] and United state Pharmacopeia [3]. From the literature review, it is observed that many analytical methods have been developed involving spectrophotometric [4][5][6][7][8][9][10][11][12][13][14], LC [14], HPLC [12,[15][16][17], Volttametry [20], HPTLC [15,[18][19], stability-indicating HPLC method [17] and LC-ESI-MS/MS [21] for the estimation of OLO in pharmaceutical formulations. Mometasone furoate (MOM) Figure 2 F I G U R E 2 Structure of Mometasone Furoate.…”
Section: Introductionmentioning
confidence: 99%
“…Olopatadine is official in Indian Pharmacopeia [2] and United state Pharmacopeia [3]. From the literature review, it is observed that many analytical methods have been developed involving spectrophotometric[4–14], LC [14], HPLC [12, 1517], Volttametry [20], HPTLC [15, 1819], stability‐indicating HPLC method [17] and LC‐ESI‐MS/MS [21] for the estimation of OLO in pharmaceutical formulations. Mometasone furoate (MOM) Figure 2, chemically [(8 S ,9 R ,10 S ,11 S ,13 S ,14 S ,16 R ,17 R )−9‐chloro‐17‐(2‐chloroacetyl)−11‐hydroxy‐10,13,16‐trimethyl‐3‐oxo‐6,7,8,11,12,14,15,16‐octahydrocyclopenta[a]phenanthren‐17‐yl] furan‐2‐carboxylate Topical glucocorticoid receptor (GR) agonist with dermatological properties.…”
Section: Introductionmentioning
confidence: 99%
“…Olopatadine is official in Indian Pharmacopoeia [2] and US Pharmacopoeia [3]. From the literature review, it is observed that many analytical methods have been developed involving spectrophotometric [4–14], LC [14], HPLC [12, 1517], voltammetry [20], HPTLC [15, 1819, 22], stability‐indicating HPLC method [17], and LC‐ESI‐MS‐MS[21] for the estimation of OLO in pharmaceutical formulations. Fluticasone propionate (FLU) Figure 1, chemically [(6 S ,8 S ,9 R ,10 S ,11 S ,13 S ,14 S ,16 R ,17 R )−6,9‐difluoro‐17‐(fluoromethylsulfanyl‐carbonyl)−11‐hydroxy‐10,13,16‐trimethyl‐3‐oxo‐6,7,8,11,12,14,15,16‐octahydrocyclopenta‐[a]phenanthren‐17‐yl] propanoate Trifluorinated Gluco‐corticoid receptor with anti‐allergic and anti‐inflammatory effect [23].…”
Section: Introductionmentioning
confidence: 99%
“…official in Indian Pharmacopoeia [2] and US Pharmacopoeia [3]. From the literature review, it is observed that many analytical methods have been developed involving spectrophotometric [4][5][6][7][8][9][10][11][12][13][14], LC [14], HPLC [12,[15][16][17], voltammetry [20], HPTLC [15,[18][19]22], stabilityindicating HPLC method [17], and LC-ESI-MS-MS [21] for the estimation of OLO in pharmaceutical formulations. Fluticasone propionate (FLU) Figure 1 thren-17-yl] propanoate Trifluorinated Gluco-corticoid receptor with anti-allergic and anti-inflammatory effect [23].…”
Section: Introductionmentioning
confidence: 99%